The Sage handbook of social media - Burgess, Jean; Marwick, Alice; Poell, Thomas (Thousand Oaks, CA : SAGE Publications Inc., 2018)
In terms of media and communication history, we are arguably in the midst of a social media paradigm. Well-known platforms like Twitter and Facebook have gone from being viewed as mere sites of teenage distraction to becoming embedded ICT infrastructure in mainstream organisations across the society, culture, and economy; such platforms, their uses, and their politics are increasingly entangled with everyday life, work, and relationships. For the past decade there has been a burgeoning interest in social media. This highly international Handbook addresses the most significant research themes, methodological approaches and debates in this field via substantial chapters specially commissioned from leading scholars coming from a range of disciplinary perspectives centered on but extending beyond the social sciences and humanities. Part One: Histories and Pre-Histories ...
Includes index.
Description based on MARC record for print version.
Keywords: Online social networks -- Handbooks, manuals, etc; Social media -- Handbooks, manuals, etc